2‐(Dimethylamino)phosphinine: A Phosphorus‐Containing Aniline Derivative. Issue 7 (14th December 2020) - Giese, Steven; Klimov, Katrin; Mikeházi, Antal; Kelemen, Zsolt; Frost, Daniel S.; Steinhauer, Simon; Müller, Peter; Nyulászi, László; Müller, Christian
Abstract: The yet unknown 2‐amino‐substituted λ 3, σ 2 ‐phosphinines are phosphorus‐containing aniline derivatives. Calculations show that the strong interaction of the π‐donating NR2 group with the aromatic system results in a high π‐density at the phosphorus atom. We could now synthesize 2‐N(CH3 )2 ‐functionalized phosphinines, starting from a 3‐N(CH3 )2 ‐substituted 2‐pyrone and (CH3 )3 Si‐C≡P. Their reaction with CuBr⋅S(CH3 )2 affords Cu I complexes with the first example of a neutral phosphinine acting as a rare bridging μ2 ‐P‐4e donor‐ligand between two Cu I centers. Our experimental and theoretical investigations show that 2‐aminophosphinines are missing links in the series of known 2‐donor‐functionalized phosphinines. Abstract : The first phosphorus‐containing 2‐aniline‐derivatives 2‐(CH3 )2 N‐6‐Si(CH3 )3 ‐phosphinine and 2‐(CH3 )2 N‐phosphinine were synthesized. In‐depth calculations reveal that resonance structures with two lone‐pairs at the phosphorus atom exist. Consequently, the heterocycles act as π‐donor‐ligands and show the rare μ2 ‐P‐4e bridging coordination mode in the corresponding Cu I ‐complexes.